Sosialisasi Bahaya Narkoba Di MTS Manba’ul Ulum Di Desa Japanan - Anna Kridaningsih; Febro Ikbal Tri Harianto; Rudi Tri Hermawan; Lucki Ariansah; Nurwarda Zakia; Rika Widyasari; Rinda Ayu Lestari; Kiki Lukiyan Nanda Sari; Muchammad Futuchal Arifin; Putri Nur Kumala Sari; Rakananda Aji Putra; Indah Nabila Nur Fadhila; Elsa Sofhia Febrianti; Nizar Hafidz Asigaf; Firman Aldian Manan; Mukhammad Dahril Kamal; Siti Nur Fadilah; Lutfi Nur Fatoni; Devy Silvia Rahmawati; Nazaretha Nazaretha; Alent Yoshe Kristanto; Sandi Pratama Anada Putri (Jurnal Nusantara Berbakti, 2024)
Drug use until now is increasingly concerning, technological advances have an impact as one of the factors in the spread of this prohibited item. Drug addicts are generally still children who are in productive age, namely teenagers aged between 15-19 years. One of the reasons is the lack  knowledge of the dangers of drugs for the health of children in productive age. Most drug addicts can have the effect of wanting to see firsthand, try and end up addicted, with the excuse of wanting to look cool, mature, strong and as a proof of solidarity between friends. This research was conducted related to socialization of the Dangers of Drug Use at Mts Manba'ul Ulum in Japanan Village. At Mts Manba’ul Ulum, we carry out counseling for 70 junior high school equivalent children. We hope that students, especially immature children, will get enough knowledge about the dangers of drugs.